1987
DOI: 10.3109/00365528709090141
|View full text |Cite
|
Sign up to set email alerts
|

Once-Daily Administration of Famotidine for Reflux Esophagitis

Abstract: S. Once-daily administration of famotidine for reflux esophagitis. Scand J Gastroenterol 1987, 22(suppl 134), 51-54 An open-labeled study of once-daily administration of 40 mg famotidine was conducted in 24 patients with endoscopically confirmed reflux esophagitis. The mean age of the patients was 62.8 years. Most had stage I or stage I1 esophagitis of 1 years' duration or less. After4,8,12, and 16 weeksof treatment, endoscopically documented healing was reported in 50%, 75%, 8296, and 83% of patients, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A study carried out in Japan has found that nizatidine (NIZ) 150 mg bid, is more effective than other histamine H2 receptor agonists (H2RAs) in treating reflux esophagitis (RE), although the Correspondence to: Katsuhiko Iwakiri, M.D., Department of Medicine, Division of Gastroenterology, Nippon Medical School, Sendagi 1-1-5, Bunkyo-ku, Tokyo 113-8603, Japan Phone: +81-3-3822-2131 Fax: +81-3-5685-1793 e-mail: k-iwa@nms.ac.jp NIZ group did include more subjects with severe RE compared with the famotidine group (Sekiguchi et al, 1983;Nakano et al, 1984;Sekiguchi et al, 1989). In addition, it has been reported that maintenance therapy from NIZ has a significantly higher non-recurrence rate than that of famotidine in patients with RE (Hamamoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out in Japan has found that nizatidine (NIZ) 150 mg bid, is more effective than other histamine H2 receptor agonists (H2RAs) in treating reflux esophagitis (RE), although the Correspondence to: Katsuhiko Iwakiri, M.D., Department of Medicine, Division of Gastroenterology, Nippon Medical School, Sendagi 1-1-5, Bunkyo-ku, Tokyo 113-8603, Japan Phone: +81-3-3822-2131 Fax: +81-3-5685-1793 e-mail: k-iwa@nms.ac.jp NIZ group did include more subjects with severe RE compared with the famotidine group (Sekiguchi et al, 1983;Nakano et al, 1984;Sekiguchi et al, 1989). In addition, it has been reported that maintenance therapy from NIZ has a significantly higher non-recurrence rate than that of famotidine in patients with RE (Hamamoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the newer H2-blockers, famotidine is a drug capable of inducing a distinct dose-related reduction of acid exposure time [ 5 31 and has already shown a promising effect in the healing of endoscopic oesophagitis [54] : in this open study, healing rates at 4, 8, 12 and 1 6 weeks were 50, 75. 82 and 83%, respectively.…”
Section: H2-receptor Antagonistsmentioning
confidence: 96%
“…24 h reflux variables before and after treatment with famotidine or ranitidine heals 82% of patients with mild esophagitis ( 61). Famotidine 40 mg bid heals 48% of patients with moderate to severe esophagitis at six weeks compared with 18% with placebo (healing rates increasing to 69 and 29% at 12 weeks) ( 62 ).…”
Section: Famotidine: Famotidine 40 Mg At Nightmentioning
confidence: 99%